CUSTOMER PROFITABILITY ANALYSIS BASIS ON ACTIVITIES AND ITS ROLE IN COST MANAGEMENT AND OPERATIONAL PERFORMANCE IMPROVEMENT: APPLIED STUDY IN GENERAL COMPANY FOR ELECTRICAL INDUSTRIES / AIR-COOLED ENGINES FACTORY - Ali Abdul-Hussein Hani Al-Zameli (Scholar Express Journals, 2023)
The research aims to study the theoretical framework of the customer's profitability and measurement the costs basis on activities and link them through analysis of customer profitability basis on activities for determining the costs and revenues of each customer and thus determine the profitability of each of them, and to show the role of this in providing appropriate information for cost management and operational performance improvement. Research applied in General Company for Electrical Industries / Air-Cooled Engines Factory for the data of the fiscal year 2021. The customer's profitability was analyzed on the basis of the activities in the research sample. The research put a set of conclusions, the most important of which was that customer profitability analysis in the General Company for Electrical Industries can help in providing appropriate information that helps in cost management and operational performance improvement in an appropriate manner to various environmental changes
Keywords: Customer profitability; customer profitability analysis based on activities; cost management